The COTEC Innovative SME Network from an economic and financial perspective - Bento, P.; Sousa, H.; Oliveira, J. (Economia Global e Gestão, 2012)
This article examines the COTEC Innovative SME Network from an economic and financial perspective. The COTEC Network is a group of companies that strives to be a reference for value creation in Portugal by adopting innovative attitudes and undertaking innovative activities. This analysis is made at the Network and sector levels. Portugal's non-financial SMEs (at the national level) are the benchmark for the Network, and the non-financial SMEs for each economic sector in the country are the benchmark for the COTEC sectors. Although the conclusions require confirmation in future research, they indicate that companies in the Network have much higher levels of economic profitability and financial robustness than Portugal's SMEs in general, both as a whole and by sector.